Effect of Fe(II) addition by ion exchange and precipitation of different semiconductors on the textural properties of 13X zeolite - Ali, Rawan H.; Zaboon, Sami M.; Abbas, Ammar S. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
This study investigated the textural properties of 13X zeolite, FeX zeolite, TiO2/FeX zeolite, ZnO/FeX zeolite, and TiO2+ZnO/FeX zeolite using nitrogen adsorption-desorption data at consistent low temperatures. The adsorption-desorption isotherm indicated that the studied materials have a type IV mesoporous structure, as defined by the International Union of Pure and Applied Chemistry. The results of nitrogen adsorption data analysis using the Langmuir, Freundlich, and Brunauer-Emmett-Teller models indicated that the data were best described by the Brunauer-Emmett-Teller model. The Barrett, Joyner, and Halenda model was used to analyze the pore size distribution, pore diameter, and average pore volume of the adsorbents. After the ion exchange and loading process, there was a notable decrease in surface area and pore size distribution values, while the reduction in pore volume was minimal. Zeolite 13X showed a larger pore diameter, suggesting that some structural damage or the formation of wider pores within the mesoporous range occurred during the ion exchange steps or modification by the addition of semiconductor oxides. In contrast, the FeX zeolite exhibited a smaller pore size, indicative of a more compact microporous structure. While the modified zeolites—TiO2, ZnO, and TiO2+ZnO—demonstrated a consistent pore structure, suggesting stable mesoporosity with a smaller pore size, this implies that some of the zeolite's pores were blocked or filled with TiO2 and ZnO particles.